Impact of worsening renal function on peak oxygen uptake in patients with acute myocardial infarction. Issue 6 (2nd March 2021) - Ogura, Asami; Izawa, Kazuhiro P.; Tawa, Hideto; Kureha, Fumie; Wada, Masaaki; Kanai, Masashi; Kubo, Ikko; Yoshikawa, Ryohei; Matsuda, Yuichi
Abstract: Aim: Worsening renal function (WRF) induced by acute myocardial infarction (AMI) is a strong predictor of cardiovascular events and mortality. Peak oxygen uptake may contribute to prognosis in AMI patients with WRF, however, the impact of WRF on peak oxygen uptake is unclear. Methods: Among 154 patients with AMI who underwent emergency percutaneous coronary intervention and participated in phase II cardiac rehabilitation, those who underwent cardiopulmonary exercise testing were consecutively enrolled. WRF was defined as a ≥20% decrease in estimated glomerular filtration rate (eGFR [ml/min/1.73 m 2 ]) from admission to that at cardiopulmonary exercise testing. The association of WRF with peak oxygen uptake was evaluated by multivariate regression analysis. The non‐WRF group was divided into two subgroups according to eGFR <60/≥60 at cardiopulmonary exercise testing, and eGFR at cardiopulmonary exercise testing and peak oxygen uptake of all three groups were compared. Results: Ninety‐four patients were enrolled in the final analysis. Multiple linear regression analysis showed that WRF was associated with peak oxygen uptake ( p = .003). Comparing the non‐WRF group with eGFR at cardiopulmonary exercise testing <60 and the WRF group, although eGFR at cardiopulmonary exercise testing was similar ( p = 1.000), peak oxygen uptake in the WRF group was significantly lower ( p = .026). Conclusion: WRF, not eGFR at cardiopulmonary exercise testing was significantly associated with peak oxygen uptake in patients with AMI. This result suggests that when considering the relationship between renal function and peak oxygen uptake, WRF must be taken into account. SUMMARY AT A GLANCE: This is a retrospective cohort study on 94 patients followed for up to 6 months in Japan showing that worsening of kidney function after acute myocardial infarction (MI) is associated with peak oxygen uptake on exercise test, and this association is independent of baseline kidney function. Thus a decline is kidney function post MI may have implications for worse outcomes than the absolute level of kidney function.